2009
DOI: 10.1158/1535-7163.mct-08-1072
|View full text |Cite
|
Sign up to set email alerts
|

Darinaparsin induces a unique cellular response and is active in an arsenic trioxide-resistant myeloma cell line

Abstract: Here, we report on the organic arsenical darinaparsin (ZIO-101, S-dimethylarsino-glutathione) and its anti-myeloma activity compared with inorganic arsenic trioxide. Darinaparsin induced apoptosis in multiple myeloma cell lines in a dose-dependent manner, and the addition of N-acetylcysteine, which increases intracellular glutathione (GSH), blocked cytotoxicity of both darinaparsin and arsenic trioxide. In contrast to arsenic trioxide, intracellular GSH does not appear to be important for darinaparsin metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
(49 reference statements)
6
33
0
Order By: Relevance
“…We have shown previously that Dar is significantly more potent than ATO at mediating apoptosis in various malignant cell lines, and is highly active against APL cells. Moreover, consistent with others, we have shown that Dar induces significantly more intracellular arsenic accumulation than ATO when both are given at equimolar arsenic concentrations (Manshouri et al, 2005a,b;Diaz et al, 2008;Matulis et al, 2009).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have shown previously that Dar is significantly more potent than ATO at mediating apoptosis in various malignant cell lines, and is highly active against APL cells. Moreover, consistent with others, we have shown that Dar induces significantly more intracellular arsenic accumulation than ATO when both are given at equimolar arsenic concentrations (Manshouri et al, 2005a,b;Diaz et al, 2008;Matulis et al, 2009).…”
Section: Introductionsupporting
confidence: 91%
“…Therefore, we hypothesized that Dar might enter the cell by this mechanism. Cotreatment with Dar and extracellular thiols can reduce intracellular arsenic accumulation and subsequent cell death in a myeloma cell line (Sakurai et al, 2006;Matulis et al, 2009), supporting our hypothesis that Dar uptake utilizes GSH uptake pathways. Structural analysis of Dar suggested that a putative arsenic-containing breakdown product could be dimethylarsino-cysteine (DMAC; Fig.…”
Section: Introductionsupporting
confidence: 77%
“…Importantly, darinaparsin is effective in ATO-resistant leukemic cell lines that overexpress multidrug-resistant protein 1/ATP-binding cassette, subfamily C, member1 (MRP1/ABCC1; refs. 3,9). Darinaparsin showed increased antiangiogenic activity in both in vitro human umbilical vascular endothelial cell microtubule formation and in vivo Matrigel plug models (10).…”
Section: Introductionmentioning
confidence: 99%
“…It may also be used as an alternative for ATO-resistant hematological malignancies as cross-resistance between these two drugs does not appear to develop. 91,[127][128][129] While Darinaparsin shows clinical promise, the underlying mechanisms by which it metabolizes and exerts its apoptotic effects have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…91 Arsenic trioxide and Darinaparsin are uptaken by different transport mechanisms, illicit somewhat differing protective responses, and they are metabolized by cells differently. 79,91,92 Darinaparsin was initially administered in IV (intravenous) form (no first-pass metabolism), but it is currently being evaluated as an orally administered medication. Current results show activity but as with all orally taken medications, first-pass metabolism could potentially limit its bioavailability.…”
mentioning
confidence: 99%